Virtual Simulation Analysis of Rigid-Flexible Coupling Dynamics of Shearer with Clearance - Hongyue Chen; Kun Zhang; Mingbo Piao; Xin Wang; Jun Mao; Qiushuang Song (Shock and Vibration)
A model for virtual simulation analysis of the rigid-flexible coupling of a shearer has been developed with the objective of addressing problems associated with lifetime mismatch and low reliability of pin rows of a scraper conveyor and the corresponding support mechanism of a shearer. Simulations were performed using the experimental roller load as stimulus. Results of the analysis demonstrate that the vertical cutting force on the roller serves to reduce the load on the plane support plates during shearer cutting, and the force on the right plane support plate is considerably smaller compared to that on the left plane support plate along the direction of motion of the shearer. Owing to action of the roller-traction load, loads acting on the two guiding support plates increase significantly along the direction of shearer motion. Mechanical characteristics of the support mechanism were determined through experiments, and the accuracy of the virtual simulation model was verified. Simultaneously, mechanical characteristics of the shearer support mechanism were studied under varying pitch and roll angles. This study was performed to provide a base for analyzing the mechanical characteristics as well as optimizing the structural design of the shearer. Through fatigue-life analysis of the support plate and subsequent optimization of the support plate structure, the life of the guide support plate was found to have been extended by approximately 1.5 times.